SOSIALISASI PEMOTONGAN KUKU DAN PEMELIHARAAN KESEHATAN KAMBING PADA ASHAR FARM DI KOTA PAYAKUMBUH - Reswati Reswati; Dwi Yuzaria; Amri Syahardi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Ashar Farm is one of the goat farming businesses in Payakumbuh City that has shown low progress. The population of Ashar Farm goats continued to decrease due to the death of sick goats or the slaughter of paralyzed goats. This phenomenon was due to farmers' need for knowledge in goat-raising management, especially health management. Goat long hoove was one of the causes of goat's feet leg disruption, which can cause infection, paralysis, and reduce the goat's productivity. This activity aimed to increase knowledge and coach farmers' skills in raising and maintaining goat health through hooves trimming training. This activity was carried out in several steps, i.e., preparation, counseling, training, and evaluation. The counseling method used was delivering material to the farmers about good farming practices and interactive discussions with farmers. Goat hooves trimming used simple equipment, which was easy to obtain nearby the farm. The activity was carried out according to the planning, and farmers participated well and enthusiastically, as seen from the many questions asked to the Team. Farmers have improved goat-raising management so that goats' health is maintained and their productivity increases. The evaluation results showed that farmers had adopted the information and knowledge conveyed by the Team during the implementation of activities, as seen from the rise in farmers' knowledge and skills. Farmers have skilled in hoove-trimming and apply it to their goats. They have also improved goat farming management so that the health of their goats is maintained and productivity increases.